Influence of low insertion torque values on survival rate of immediately loaded dental implants: A systematic review and meta-analysis - Darriba, Iria; Seidel, Anna; Moreno, Federico; Botelho, Joao; Machado, Vanessa; Joao Mendes, Jose; Leira, Yago; Blanco, Juan (Journal of Clinical Periodontology, 2022)
Aim: The aim was to systematically evaluate the effect of low insertion torque values on the survival rate of immediately loaded dental implants. Materials and Methods: The protocol was registered with PROSPERO (ID CRD42020189499). An electronic search was performed in PubMed, Embase, Web of Science, and Cochrane Central Register of Controlled Trials until June 2022 in English and Spanish. Studies analysing the failure or survival rate of immediately loaded dental implants according to different insertion torque values were included. Results: Five-hundred seventy-three articles were assessed for eligibility, of which seven articles, four randomized clinical trials (RCTs), one controlled clinical trial, and two prospective case series studies were included in the qualitative analysis. The RCTs were classified as having low risk of bias and the non-RCTs as having moderate and serious risk of bias. The mean survival rate for implants with low insertion toque (≤35 Ncm) was 96% (p >.001, 95% confidence interval [CI]: 0.91–0.98) and that for implants with medium or high insertion torque (>35 Ncm) was 92% (p >.001, 95% CI: 0.86–0.96) (incidence rate ratio [IRR] = 1.05, 95% CI: 0.79–1.39, p =.175, I2 = 0.0%). Splinted implants with insertion torque >20 Ncm and single implants with insertion torque >35 Ncm had a higher survival rate than implants with lower insertion torque values (IRR = 1.05, 95% CI: 0.78–1.43, p =.956, I2 = 0.0%, and RR = 0.92, 95% CI: 0.48–1.75, p =.799, I2 = 0.0%, respectively). Different insertion torque values achieved equivalent outcomes. The mean follow-up was 24 months. Conclusions: Low insertion torque values have no significant effect on survival rates of immediate loading implants at a mean follow-up of 24 months.
CRIS-Team Scopus Importer:2022-11-04
Keywords: dental implants; immediate loading; insertion torque